2021
DOI: 10.1017/s0954579421000389
|View full text |Cite
|
Sign up to set email alerts
|

Second-by-second infant and mother emotion regulation and coregulation processes

Abstract: Context-appropriate infant physiological functioning may support emotion regulation and mother–infant emotion coregulation. Among a sample of 210 low-income Mexican-origin mothers and their 24-week-old infants, dynamic structural equation modeling (DSEM) was used to examine whether within-infant vagal functioning accounted for between-dyad differences in within-dyad second-by-second emotion regulation and coregulation during free play. Vagal functioning was captured by within-infant mean and variability (stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 90 publications
(233 reference statements)
1
16
0
Order By: Relevance
“…are influenced by each other (Somers et al, 2021), and this conclusion is consistent with transactional models of emotional development (e.g., Sameroff, 2010). Despite the historical prioritization of parent-driven effects (even within bidirectional models; e.g., Belsky, 1984), fetal neurodevelopment appears to prepare the infant for the emotional communication required to actively engage in caregiver-child interactions (Cole, 2016;Gingras et al, 2005;Reissland et al, 2011).…”
supporting
confidence: 67%
“…are influenced by each other (Somers et al, 2021), and this conclusion is consistent with transactional models of emotional development (e.g., Sameroff, 2010). Despite the historical prioritization of parent-driven effects (even within bidirectional models; e.g., Belsky, 1984), fetal neurodevelopment appears to prepare the infant for the emotional communication required to actively engage in caregiver-child interactions (Cole, 2016;Gingras et al, 2005;Reissland et al, 2011).…”
supporting
confidence: 67%
“…Moreover, supporting communication is increasingly occurring via texts with others outside of close relationships (Shu et al, 2021). Nevertheless, future research should investigate whether the current results can be replicated in different types of relationships such as among couples (Bar-Kalifa et al, 2021), between leader and follower (Vasquez et al, 2020), or between parent and child (Somers et al, 2021). Furthermore, Rains et al (2016) found that reduced social cues in online text-based communication increased the recipient’s motivation to process support message content itself and that this led support messages to have a greater impact than face-to-face communication.…”
Section: Discussionmentioning
confidence: 98%
“…Second, the time‐lag (30 s) of RSA sampling in our study may be too slow to capture the caregiver–infant coupling within the fast‐acting autonomic system. Recent methodological advancements have made it possible to model RSA dynamics at the second‐by‐second level (Abney et al, 2021; Ravindran et al, 2021; Somers et al, 2021) and may be considered by future studies to capture fluctuations in parasympathetic activity on a shorter time interval. Nevertheless, the appropriate timescale (if any) has yet to be determined (Davis et al, 2018; Depasquale, 2020).…”
Section: Discussionmentioning
confidence: 99%